DISTORSI KAPITALIS TERHADAP AMERICAN DREAMS DALAM CERPEN MISS U.S.A, EMMA KNIGHT KARYA STUDS TERKEL - Anwar, Desvalini (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2009)
This paper discusses ‘Miss USA, Emma Knight’, a short story written by Studs Terkel. The analysis of the story reveals how the industries of capitalism through the discourse of beauty contest has distorted the meaning of American Dreams in order to gain and accumulate as much profit as possible. Miss Universe Incorporated, as the representation of the capitalist in this analysis, has in such a way intimidated and exploited ‘its worker’, Emma Knight, the beauty queen of Miss USA to overwork nights and days, as if she were a money machine. However, at the same time, this beautiful intelligent queen, whose personal meaning of American Dreams differs from those of the mainstreams’, takes the opportunity of being a queen to show her own meaning of the dreams. Thus she takes her responsibilities of being Miss USA on her own terms.